Esports and the Media Challenges and Expectations in a Multi-Screen Society - Torres-Toukoumidis, Angel (Routledge Focus on Digital Media and Culture, 2022)
This book takes a multidisciplinary approach to the question of esports and their role in society. A diverse group of authors tackle the impact of esports and the ways in which it has grown within the entertainment industry around the world. Chapters offer a coherent response to the following questions: What role do esports play in the entertainment industry? What communication skills can be learned through esports? What do the media gain from broadcasting esports? What is the relationship between social networks and esports? What are the main marketing strategies used in esports? What effect does communicative globalization have on the development of esports? What is the relationship between merchandising and esports? What do communication experts think about esports? Offering clear insights into this rapidly developing area, this volume will be of great interest to scholars, students, and anyone working in game studies, new media, leisure, sport studies, communication studies, transmedia literacy, and digital culture.